An Access Control Method with Subject-Object Key and Time Stamp - Islam, Md. Rafiqul (Malaysian Journal of Computer Science, 2003)
An access control method with subject-object key and time stamp is proposed. In this method each subject and object is assigned one key respectively. The key of a subject or an object can be used to reveal the access rights to the objects depending on the value of time stamp. The method achieves full dynamism. The operations of changing an access right, inserting a subject or an object and deleting a subject or an object need only modification of one key.